Особливість протоколу B.A.T.M.A.N для організації wi-fi mesh мереж - Ворончихін, О. А.; Акіменко, А. С. (ХНУРЕ, 2023)
The advantages of the wireless Mesh network compared to other networks are shown. The features of the 802.11s standard for the organization of a Mesh network are analyzed. An overview of the features of using the B.A.T.M.A.N protocol, which is divided into protocols of the second and third routing levels, was conducted. The main parameters on which the B.A.T.M.A.N protocol is based and the principle of its action are considered.